Prognostic value of self-reported fatigue on overall survival in patients with myelodysplastic syndromes: a multicentre, prospective, observational, cohort study. Issue 15 (November 2015) - Efficace, Fabio; Gaidano, Gianluca; Breccia, Massimo; Voso, Maria Teresa; Cottone, Francesco; Angelucci, Emanuele; Caocci, Giovanni; Stauder, Reinhard; Selleslag, Dominik; Sprangers, Mirjam; Platzbecker, Uwe; Ricco, Alessandra; et al.
Summary: Background: The clinical presentation of myelodysplastic syndromes is highly variable and so accurate prediction of outcomes in these patients is crucial. We aimed to assess whether self-reported fatigue severity predicts overall survival beyond gold-standard prognostic indices in patients with higher-risk myelodysplastic syndromes. Methods: We did a multicentre, prospective, observational, cohort study of patients from 37 centres in Europe, USA, and east Asia. Adults (≥18 years) with myelodysplastic syndromes were consecutively enrolled within 6 months of diagnosis with an intermediate-2-risk or high-risk score according to the International Prognostic Scoring System (IPSS). Patients were enrolled irrespective of older age, comorbidities, performance status, and progression from a lower IPSS risk score category. All patients had to complete a quality of life assessment at baseline. With use of univariate and then multivariate Cox proportional hazards regression analysis, we constructed a multivariate model of how prognostic variables, including IPSS and fatigue score from the European Organisation for Research and Treatment of Cancer quality-of-life questionnaire–core 30, predicted overall survival. The primary endpoint was overall survival by baseline self-reported fatigue scale ratings. This study was registered withClinicalTrials.gov, numberNCT00809575 . Findings: Between Nov 10, 2008, and Aug 13, 2012, we enrolled 280 patients with a median age of 71 years (IQR 64–77). The median follow-up was 15 months (IQR 8–27), and the last patient was assessed Feb 16, 2015. The median overall survival from diagnosis was 17 months (95% CI 15–19). In univariate analysis, the baseline factors that were significantly associated with reduced overall survival were increasing age, transfusion dependency (defined as having received at least one red blood cell transfusion every 8 weeks over a period of 4 months), Eastern Cooperative Oncology Group (ECOG) performance status of two or more, increased white blood cell count, high-risk IPSS score, and higher self-reported fatigue severity. In multivariate analysis, baseline factors independently associated with reduced overall survival were high-risk IPSS score (hazard ratio [HR] 2·525, 95% CI 1·357–4·697; p=0·0035) and a higher score for fatigue (1·110, 1·040–1·170, for every ten points of fatigue deterioration; p=0·0007). In further multivariate models for survival, including either the WHO-based prognostic scoring system or the revised version of the IPSS classification, fatigue remained a statistically significant independent prognostic factor with a HR of 1·120 (1·050–1·180, p=0.0003) and a HR of 1·130 (1·060–1·190, p=0·0002), respectively. Interpretation: In patients with newly diagnosed higher-risk myelodysplastic syndromes, self-reported fatigue severity provides prognostic information for survival independent from gold-standard risk classifications. Our findings suggest that fatigue assessment should be included in routine diagnostic investigation for these patients and considered as a standard baseline stratification factor in future randomised controlled trials. Funding: Associazione Italiana contro le Leucemie, Linfomi e Mieloma (AIL).